2006
DOI: 10.1590/s0100-69912006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da função respiratória em indivíduos submetidos à abdominoplastia

Abstract: OBJETIVO: Avaliar a função respiratória em indivíduos submetidos à abdominoplastia, através de parâmetros espirométricos. MÉTODO: Estudo prospectivo de 33 mulheres hígidas e não tabagistas, submetidas à abdominoplastia, e com resultados normais para as radiografias de tórax realizadas antes e quatro dias após a operação. Foram realizadas provas espirométricas no pré-operatório, no quarto, 15o e no 30o dias de pós-operatório. RESULTADOS: Provas espirométricas evidenciaram que, exceto pela relação VFE1/CVF e FEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…These values increased on the seventh day, returning to normality on the fifteenth day, revealing a curve similar to what occurs in the spirometry evaluations found in prior studies. [12][13][14] The results are not surprising considering that with the exception of the internal intercostal muscles, all other muscles involved in forced expiration are abdominal wall muscles. As previously described, the rectus abdominis and external oblique were sutured during the procedure.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…These values increased on the seventh day, returning to normality on the fifteenth day, revealing a curve similar to what occurs in the spirometry evaluations found in prior studies. [12][13][14] The results are not surprising considering that with the exception of the internal intercostal muscles, all other muscles involved in forced expiration are abdominal wall muscles. As previously described, the rectus abdominis and external oblique were sutured during the procedure.…”
Section: Discussionmentioning
confidence: 78%
“…If this was the case, it would also explain why the VEF1 was not altered (since the expiratory muscles function remained the same). Other studies 11,12,14,28,47 did not reveal the increase in the FVC.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Tercan et al 10 evaluated 14 healthy women who underwent abdominoplasty, observing a significant decline in FVC on POD 10 and subsequent improvement by POD 30, when FVC surpassed the preoperative values, suggesting that correction of diastasis recti abdominis promotes effective containment of the abdominal wall, improving the spirometric parameters over a period > 30 days. Similarly, Helene Junior et al 13 found that, among patients undergoing abdominoplasty, the values of FEV 1 , FVC, FEF 25-75% , and PEF were lower on POD 4 than in the preoperative period, the FEV 1 /FVC ratio remaining constant, although FEV 1 and FVC were both below normal, suggesting a restrictive pattern. The authors also found that FVC and PEF showed significant improvement from POD 4 to POD 15, as well as from POD 15 to POD 30, although neither returned to the preoperative value.…”
Section: Discussionmentioning
confidence: 88%